Concept Mapping: An Innovative Tool to Teach Critical Community Health Nursing Using the Example of Population Health Promotion - Dosani, Aliyah; Lind, Candace; Loewen, Sylvia (Witness: The Canadian Journal of Critical Nursing Discourse, 2019)
Introduction: Concept mapping is a tool that is used to visualize complex factors and the links between them. While concept mapping is represented in community health practice and research literature, we found little information about using concept mapping in community health nursing education. Background: We developed an innovative concept map assignment to assist students to visualize complex inter-related factors and begin thinking about appropriate and relevant nursing interventions, using the Population Health Promotion Model (PHPM). Discussion: Concept maps enhanced the quality of meaningful teaching and learning at the university level, acting as both a learning and assessment strategy. Students exhibited critical thinking and drew conclusions that involved larger systemic issues such as social justice and health equity. Conclusion: Concept mapping is a powerful tool that facilitates and assesses authentic student learning. The concept map assignment was also an effective tool to help students grasp and apply the PHPM.